COMPARISON OF DEPRESSION, ANXIETY AND STRESS SCORE AMONG CLINICAL AND NON-CLINICAL HEALTHCARE WORKERS DURING THE COVID-19 PANDEMIC - Iqbal, Mishal; Iqbal, Mehak; Iftikhar, Nadia; Inam, Syed Hashim Ali; Jamil, Hamza; Nisar, Shazia (Pakistan Armed Forces Medical Journal, 2021)
Objective: To assess the psychological impact of COVID-19 pandemic on healthcare workers.Study Design: Cross sectional study.Place and duration of Study: Armed Forces Institute of Cardiology/National Institute of Health Diseases in June 2020.Methodology: A total of 317 healthcare professionals, of different designations, affiliated with different public and private sector hospitals in Pakistan participated in this project. They were asked to complete Depression, anxiety and stress scales-42 (DASS-42).Results: Out of 317 healthcare workers, 107 (33.75%), 111 (35.02%), 103(32.49%) were depressed, anxious and stressed respectively. Female gender was associated with a higher prevalence of depression, anxiety and stress.Conclusion: More than one third of healthcare workers were depressed, anxious or stressed during the COVID-19 pandemic. Two out of five female healthcare workers were suffering from depression, anxiety or stress.Keywords:,  , .